Indirect effect of 7-valent pneumococcal conjugate vaccine on pneumococcal carriage in newborns in rural Gambia: a randomised controlled trial - Egere, U; Townend, J; Roca, A; Akinsanya, A; Bojang, A; Nsekpong, D; Greenwood, B; Adegbola, R; Hill, P (Public Library of Science, 2012)
BACKGROUND: Gambian infants frequently acquire Streptococcus pneumoniae soon after birth. We investigated the indirect effect of 7-valent pneumococcal conjugate vaccine (PCV-7) on pneumococcal acquisition in newborn Gambian babies. METHODS: Twenty-one villages were randomised to receive PCV-7 to all subjects (11 vaccinated villages) or to infants aged 2-30 months (10 control villages). Other control villagers received Meningococcal C conjugate vaccine. From 328 babies born during the trial, nasopharyngeal swabs were collected after birth, then weekly until 8 weeks of age when they received their first dose of PCV-7. Pneumococcal carriage and acquisition rates were compared between the study arms and with a baseline study. RESULTS: 57.4% of 2245 swabs were positive for S. pneumoniae. Overall carriage was similar in both arms. In vaccinated villages fewer infants carried pneumococci of vaccine serotypes (VT) (16.9% [31/184] vs. 37.5% [54/144], p<0.001) and more carried pneumococci of non-vaccine serotypes (NVT) (80.9% [149/184] vs. 75.7% [109/144], p = 0.246). Infants from vaccinated villages had a significantly lower acquisition rate of VT (HR 0.39 [0.26-0.58], p<0.001) and increased acquisition of NVT (HR 1.16 [0.87-1.56], p = 0.312). VT carriage (51.6% vs. 37.5%, p = 031 in control and 46.1% vs. 16.8%, p<0.001 in vaccinated villages) and acquisition rates (HR 0.68 [0.50-0.92], p = 0.013 in control villages and HR 0.31 [0.19-0.50], p<.001 in vaccinated villages) were significantly lower in both study arms than in the baseline study. NVT carriage (63.2% vs. 75.7%, p = 0.037 in control and 67.2% vs. 75.3%, p = 0.005 in vaccinated villages) and acquisition rates (HR 1.48 [1.06-2.06], p = 0.022) and (HR 1.52 [1.11-2.10], p = 0.010 respectively) were significantly higher. CONCLUSION: PCV-7 significantly reduced carriage of VT pneumococci in unvaccinated infants. This indirect effect likely originated from both the child and adult vaccinated populations. Increased carriage of NVT pneumococci needs ongoing monitoring. TRIAL REGISTRATION: ISRCTN Register 51695599.